E a vida, como vai?: avaliação da qualidade de vida de um grupo de idosos portadores de doenças crônicas não transmissíveis vinculados a um programa de promoção da saúde - Manso, Maria Elisa Gonzalez (2009)
The Brazilian Supplemental Health System, due to its compulsory legislation, aiming for an improved innovative health service, as well as cost cutting, has been implementing programs of health improvement, disease, and risk prevention. These programs were based on demographic and epidemiological data that show that non transmissible chronic diseases are thoroughly related to elderly mortality and morbidity and the increasing use of health services by this specific group. The health improvement program based on principles of attention integrality, department cooperation, equality, participation, group-work and sustainability seeks health management people autonomy, being intrinsically related to WHO principles concerning active aging. By this approach, the term quality-of-life, as a social and historic process, gets shaped. This research is presented aiming to appraise quality-of-life of a group of elders, all chronic degenerative disease bearers associated to a health improvement program sponsored by a health insurance company. With specific goals, we intend to establish a socialdemographic and morbidity profile to test an instrument that allows us to measure quality-of-life concept understanding, to learn the interpretation the elders attribute to the quality-of-life concept, to verify if these elders acknowledge the NTCD they suffer from to affect their qualityof- life and how they see the program s contribution to the last. The chosen methodology aims to be faithful to the proposed methodological base, and in doing so, it employs a combination of quantity and quality methods. For the quantity methods, we understand the use through three surveys: social-demographic aspects, WHOQOL-OLD and WHOQOL-BREF. On the other hand, the quality stage was based on semi-structured interviews. Twenty-four elders took part in the quantity research. These elders are associated with a health improvement program created in 2009 by a health insurance company, which is based on cooperative medical work, belongs to UNIMED system, and is located in the city of Sao Paulo. In the quality stage, 13 elders were interviewed. It was established that most of the group was composed of female elders with an average age of 73; however, men who participated were older and sicker. Most are retired, well educated, married and have more than one non transmissible chronic disease. The group sees their quality-of-life as good or very good, being physically satisfied with their health. The lowest scores in the different fields that compose the WHOQOL modules were associated with factors as age below 70, being a widower, living alone, being highly educated, being a smoker and being hospitalized. The group associates quality-of-life mainly with well being and social integration highlighting that the chronic diseases affect it by restricting their activities, these, however, are able to overcome. The program participation is evaluated as providing well being, social integration opportunity and learning. It is noticed the importance the group asserts to autonomy. It is believed that this research has achieved its proposed goals; however, there are areas that require a deeper study yet